Structure and assembly model for the Trypanosoma cruzi 60S ribosomal subunit - Liu, Zheng (Proc Natl Acad Sci U S A, 2016)
Ribosomes of trypanosomatids, a family of protozoan parasites causing debilitating human diseases, possess multiply fragmented rRNAs that together are analogous to 28S rRNA, unusually large rRNA expansion segments, and r-protein variations compared with other eukaryotic ribosomes. To investigate the architecture of the trypanosomatid ribosomes, we determined the 2.5-Å structure of the Trypanosoma cruzi ribosome large subunit by single-particle cryo-EM. Examination of this structure and comparative analysis of the yeast ribosomal assembly pathway allowed us to develop a stepwise assembly model for the eight pieces of the large subunit rRNAs and a number of ancillary “glue” proteins. This model can be applied to the characterization of Trypanosoma brucei and Leishmania spp. ribosomes as well. Together with other details, our atomic-level structure may provide a foundation for structure-based design of antitrypanosome drugs.